Consumption and wage humps in a life-cycle model with education - Holger Kraft; Claus Munk; Frank Thomas Seifried; Mogens Steffensen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
The observed hump-shaped life-cycle pattern in individuals' consumption cannot be explained by the classical consumption-savings model. We explicitly solve a model with utility of both consumption and leisure and with educational decisions affecting future wages. We show optimal consumption is hump shaped and determine the peak age. The hump results from consumption and leisure being substitutes and from the implicit price of leisure being decreasing over time; more leisure means less education, which lowers future wages, and the present value of foregone wages decreases with age. Consumption is hump shaped whether the wage is hump shaped or increasing over life.
Keywords: D11; D14; D91; I21; J24; 330; education; leisure; consumption hump; wage hump